Replacement of related POU transcription factors leads to severe defects in mouse forebrain development. - Sock, Elisabeth; Reiprich, Simone; Müller, Jana; Stolt, Claus; Wegner, Michael; et al. (Developmental Biology, 2009)
Related transcription factors of the POU protein family show extensive overlap of expression in vivo and exhibit very similar biochemical properties in vitro. To study functional equivalence of class III POU proteins in vivo, we exchanged the Oct-6 gene by Brn-1 in the mouse. Brn-1 can fully replace Oct-6 in Schwann cells and rescue peripheral nervous system development in these mice. The same mice, however, exhibit severe defects in forebrain development arguing that Oct-6 and Brn-1 are not functionally equivalent in the central nervous system. The cause of the observed forebrain phenotype is complex, but anteriorly expanded Wnt1 expression contributes. Oct-6 normally represses Wnt1 expression in the early diencephalon and replacement by Brn-1 as a weaker inhibitor is no longer sufficient to maintain the necessary level of repression in the mouse mutant. The extent of functional equivalence between related transcription factors is thus strongly dependent on the analyzed tissue. © 2009 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.med.IB.LPCIPDBI.replac
Keywords: Brain malformation; Brn-1; Functional equivalence; Homeodomain; Oct-6; Redundancy; Transcription factor; Wnt signalling